1987
DOI: 10.1111/j.1365-2044.1987.tb03081.x
|View full text |Cite
|
Sign up to set email alerts
|

Premedication for day case surgery

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…This finding is supported by previous placebo-controlled studies using several doses of midazolam [21], triazolam and diazepam [22], in which only the largest doses produced measurable anxiolysis, while psychomotor impairment was evident at lower doses [22]. One might question whether the specific anxiolytic effect attributed to BZDs in their role as anaesthetic premedication is not merely a result of generalised CNS depression.…”
Section: ó 2002 Blackwell Science Ltdsupporting
confidence: 58%
“…This finding is supported by previous placebo-controlled studies using several doses of midazolam [21], triazolam and diazepam [22], in which only the largest doses produced measurable anxiolysis, while psychomotor impairment was evident at lower doses [22]. One might question whether the specific anxiolytic effect attributed to BZDs in their role as anaesthetic premedication is not merely a result of generalised CNS depression.…”
Section: ó 2002 Blackwell Science Ltdsupporting
confidence: 58%
“…However, other workers have found that either placebo produced comparable effects to 0.3mg.kg-' (15) or 0.6mg.kg-' (16) of midazolam, or that after 0.75 mg.kgp' recovery from anaesthesia was impaired (17). In adults oral premedication with 15 mg of midazolam may delay recovery and discharge from hospital (18). A 0.75 mg.kg-' dose of midazolam was chosen for this study as it had been previously shown to be an effective preanaesthetic medication without causing excessive postoperative sedation (13).…”
Section: Discussionmentioning
confidence: 99%
“…Midazolam has been used for sedation by intramuscular (IM),[567] rectal,[8910] oral[111] and sublingual routes,[1213] but each has its own advantages and disadvantages. IM administration, although effective, is not well accepted by children because children have a natural fear for syringes and needles, and also causes distressing pain to children.…”
Section: Introductionmentioning
confidence: 99%